TEKNOLOGI SILASE JERAMI JAGUNG HIBRIDA SEBAGAI PAKAN TERNAK DI NAGARI TUIK IV KOTO MUDIEK KECAMATAN BATANG KAPAS KABUPATEN PESISIR SELATAN - Afrijon Afrijon; Murnita Murnita; Gusriati Gusriati (Jurnal Hilirisasi IPTEKS, 2023)
The feed is a very important aspect to support the success of a livestock business. Ruminant livestock relies heavily on forage. The availability of forage fluctuates greatly, being abundant in the rainy season and scarce in the dry season. Corn stover (straw) is one of the agricultural by-products that has the potential to be used as a substitute for ruminant animal feed. The purpose of this activity is: (1) Socializing farmers' efforts to use hybrid corn straw as animal feed (silage), and (2) Increasing farmers' knowledge and skills in using hybrid corn straw as animal feed (silage). This activity took place in Nagari Tuik IV Koto Mudiek, Batang Kapas District, Pesisir Selatan Regency. The methods used are: Provision, Coordination, Taking students to the location, Socialization and Counseling, Practice, Monitoring, Assessment and Follow-up. The results of hybrid corn straw silage technology as animal feed are an increase in the knowledge and skills of cattle breeders regarding the aspect of animal feed in the form of silage, which is sourced from agricultural waste, namely hybrid corn straw with the addition of brown sugar and fine bran. As proof of success, it can be seen from partners actively participating in training and committing to making animal feed (silage) again, namely 100%, and partners gain a good understanding of animal feed, silage, benefits, advantages, deficiencies and functions of additives as well as skills in processing and re-making silage from corn straw increased on average by 88.75%.